PERAN QATAR SEBAGAI MEDIATOR DALAM REKONSILIASI KONFLIK DI AFGHANISTAN PADA TAHUN 2013 - 2021 - Cevy, Abi Ichsan; Batubara, Amligo (Kajian Ilmu Sosial (KAIS), 2022)
In recent years, Qatar has become a role model as a state actor who can become a mediator in the territory of conflict countries. This article analyzes the role of Qatar as a mediator in the reconciliation of conflicts in Afghanistan in the 2013-2021 period, namely Qatar as a mediator from the United States and militant groups in Afghanistan. The purpose of this article is to describe and analyze the effectiveness of Qatar's foreign policy in realizing conflict reconciliation and ending the war in Afghanistan. This study uses qualitative research methods by collecting data through literature study and triangulation. Data were collected and analyzed using a descriptive-analytical approach. This research analysis uses role theory to see the level of effectiveness of Qatar's foreign policy in resolving the conflict in Afghanistan. Since for now the US and its allies have withdrawn all troops from Afghanistan and made the Taliban lead the country, role theory can look at how the factors that could ultimately lead both sides to end the war in Afghanistan. One of the factors is Qatar's mediating role which has pushed in conflict resolution to reach a peace agreement between the two sides and end the 20-year war in Afghanistan.